Pengaruh Pemberian Puding Susu Buah Naga Merah (Hylocereus Polyrhizus) Terhadap Kadar Glukosa Darah Puasa Pasien Diabetes Mellitus Tipe 2 - Nunung Setyani; Ni Ketut Sri Sulendri; Fifi Lutfiah; Suhema Suhaema (Poltekkes Kemenkes Mataram, 2019)
Background: One of the typical signs of diabetes mellitus (DM) is hyperglycemia, which is one medical condition that consists of increasing hormone levels within normal limits. Basic Health Research Results in 2018 DM prevalence in Indonesia increased from 6.9% in 2013 to 8.5% in 2018 (Ministry of Health, 2018). One of the nutritional therapies for the management of diabetes mellitus is fiber consumption. Fruit which contains high fiber, one of which is dragon fruit. Research by Wiardani et al., (2014) provides dragon fruit juice 200 grams of blood glucose levels in DM patients with an average decrease in Prondrial 2 hours Post blood calcium level (2JPP) of 79.1 mg / dL and research by Hidayati (2017) ) by giving red dragon fruit 200 grams of reduction in fasting blood by 19.1 mg / dL.Purpose :To determine the difference in levels of red dragon fruit (hylocereus polyrhizus) against decreasing fasting blood glucose levels of type 2 diabetes patien Method: Research quasy experimental pre post test with control group. Results: The results of the statistical analysis paired with the t-test in the assessment group showed differences in the fasting blood levels of the pretest-posttest with a p value of 0.008 (p <0.05), meaning that it was consistent with contributions related to blood count before and replacement. The results of the independent t-test showed that there was no difference in the difference between fasting blood levels in the advisory group and the control group that discussed the p value of 0.070. (p> 0.05).Conclusion: There is no contribution of giving red dragon fruit milk pudding (Hylocereus polyrhizus) to the reduction of blood glucose levels of type II diabetes mellitus patients.